The Predicaments of Childless Women in Nigerian Fiction: A Womanist Reading of Flora Nwapa’s One Is Enough and Lola Shoneyin’s The Secret Lives of Baba Segi’s Wives - GBAGUIDI, CELESTIN; Dadja-Tiou, Panaewazibiou; GADE, Maurice (My University, 2022)
Using womanist literary criticism, this work has critically analyzed and revealed that women’s worth is tied to their ability to bear children. The study has also examined the plight, predicaments, and abuses of childless women in African culture. The paper has revealed that childless women are verbally abused, physically beaten, psychologically abused, and maltreated. The paper argues that it is unethical and immoral to maltreat childless women for involuntary infertility. The pressures coming from society constitute huge struggles for childless women when they fail to bear children after a couple of times. The emotional turmoil is further compounded by societal pressure. Family members compel the husband to take another wife for the sake of ensuring a continued lineage. In some cultures, these women suffer domestic abuse, and divorce and are even driven out of their marital homes. The plight of childless women is unfathomable in most African societies with regard to how society maltreats these women because of their incapacity of bearing children. Furthermore, the study has revealed that the social pressures and their predicaments have nevertheless become an impetus for these childless women’s self-actualization and self-realization. Hard work and self-reliance become imperative for these childless women if they really yearn for social thriving.
Keywords: Abuse; African Societies; Childless Women; Predicament.